Analisis Kapabilitas Proses Produk Roti Menggunakan Metode Six Sigma pada Home Roti Skala UMKM - Naila Harmalia Balqis; Ulfa Ainul Lathifah; Kherlin Bunga Safira; Erliana Putri; Riska Fii Ahsani (Jurnal EMT KITA, 2026)
Quality consistency in small-scale bread production within SMEs is often challenged by process variability, which affects efficiency and product standards. This study aims to analyze process capability and quality control in bread production using the six sigma approach. A descriptive quantitative method was employed, utilizing production and defect data collected through observation, documentation, and interviews during the period of January – December 2025.Process performance was evaluated using defect per million opportunities (DPMO), sigma level analysis, p-control charts, pareto diagrams, and cause-and-effect (fishbone) diagrams. The result indicate a defect rate of 2.36%, with a DPMO value of 7.870 and sigma level of 3.93, suggesting that the process operates at a moderate capability level and has not yet reached optimal six sigma standar. The most dominant defect include under-expanded bread, burnt products, and non-standard shapes, with primary causes related to human and method factors. Improvement recommendations focus on standardizing fermentation processes, controlling baking temperature and time, and enhancing operator skills through training, with a targeted reduction of defect rates to below 2% and an increase in sigma level toward >4.These findings provide practical implications for SME-scale bread industries in improving product quality consistency , reducing process variability, and strengthening business competitiveness through data-driven quality control implementation.